A two-echelon supply chain model with deterioration and stock-dependent demand via forward and backward stocking policies. (11th June 2022) - Kumar, M. Ganesh; Uthayakumar, R.
We have developed an integrated inventory model for deteriorating items in a two-echelon supply chain. In this model, we have assumed that the vendor produces a single product at a constant rate and transferred it in equal batches to buyer's warehouse. Some of the products are presented to the customer in the buyer display area and the demand is assumed to be positively dependent on the products displayed. Due to deterioration, the vendor incurs a warranty cost for each deteriorated item. We compared the total profit for both forward and backward stock policy, and we showed that the holding cost decreases as the stock moves downstream, the vendor has to adhere to the forward stock policy. The aim is to determine the number of deliveries needed to transfer, lot size such that the average profit of the system attains its maximum. Numerical examples are provided for illustrating the model.